Constraints and demands on public finances: Considerations of resilient fiscal policy - Rawdanowicz, Łukasz (OECD Economics Department Working Papers, 2021)
Over the past several decades, public debt has increased substantially in many OECD countries, particularly in the aftermath of recessions. The extent of this increase and the resulting debt levels varied across countries, partly reflecting differences in average budget balances. Despite rising debt, governments' interest payments as a share of GDP have declined, reducing concerns about debt sustainability. Still, high debt levels make public finances vulnerable to negative shocks. Thus, governments will have to balance the need to minimise the risk of fiscal stress and the need to satisfy growing demands on public finances related to population ageing, climate change, low growth, inequalities, accelerated digitalisation and cyclical demand stabilisation. Limitations of various numerical indicators of debt sustainability give some support to a more qualitative assessment of fiscal policy and stress the importance of effective and resilient fiscal frameworks. Credible and transparent fiscal frameworks can help make appropriate policy choices, which are affected by numerous political biases and constraints. However, such frameworks do not guarantee positive outcomes. Further research on interactions between various elements of such frameworks, such as fiscal rules, medium‑term expenditure plans, budget transparency and independent fiscal institutions, is needed